Biochemical Alterations and Fertility Response to Ovsynch Protocol in Repeat Breeding Crossbred Cows with Prolonged Estrus - Patel, Dhaval N.; Nakhashi, Haresh C.; Sutaria, Tarun V.; Chaudhari, Ravji K.; Chauhan, Prakash M. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was conducted to determine the biochemical profile and fertility response in repeat breeder crossbred cows having normal and prolonged estrus by using ovsynch protocol. Total 20 crossbred cows, not conceiving even after more than four services were selected from the semi-arid area of Banaskantha district in Gujarat. They were divided into two equal groups: Group-I (n=10) - cows with prolonged estrus period (>28 hrs) and Group-II (n = 10) - cows with normal estrus period (18 to 28 hrs). The animals of both groups were treated with ovsynch protocol starting from 5th day of estrous cycle using GnRH-PG-GnRH (20, 500 and 20 μg) on day 0, 7 and 9 with FTAI on day 10. The blood was collected on day 0, 7th, 9th, and 25th (15th day post-FTAI) of the treatment to determine plasma glucose, total protein and total cholesterol. Pre-treatment mean duration of estrus in Group-I and Group-II cows was 84.60 ± 5.35 and 25.60 ± 2.79 hrs, respectively, and it declined significantly (p <0.05) following ovsynch treatment (39.80 ± 5.56 hrs) in Group-I, although estrous cycle lengths were identical in both the groups. The conception rates in group I and II were 60 and 70%, respectively. The cows with prolonged estrus had significantly lower mean blood glucose concentration than those with normal estrus, and the level was also significantly lower on day 9th (induced estrus) in both the groups. The plasma total protein concentration was significantly lower on 0, 9th, and 25th day in Group-I than in Group-II. A non-significant difference existed for protein levels within the conceived crossbred cows, whereas the difference was significant within non-conceived crossbred cows. The overall plasma cholesterol concentration was nonsignificantly higher in Group-I than the Group-II. Blood glucose, plasma protein and plasma total cholesterol concentrations differed non-significantly between the conceived and non-conceived crossbred cows at all periods in both the groups.